Ultrafast THz photophysics of solvent engineered triple-cation halide perovskites - Kumar, Abhishek (2019)
Solution processed thin film organic-inorganic perovskites are key to the large scale manufacturing of next generation wafer scale solar cell devices. The high efficiency of the hybrid perovskite solar cells is derived mainly from the large carrier mobility and the charge dynamics of films, which heavily depend on the type of solvent used for the material preparation. Here, we investigate the nature of conduction and charge carrier dynamics of mixed organic-inorganic cations [methylammonium (MA), formamidinium (FA), and cesium (Cs)] along with the mixed halides [iodine (I) and bromine (Br)] perovskite material [Cs0.05(MA0.17FA0.83)0.95Pb(I0.83Br0.17)3] synthesized in different solvents using optical pump terahertz probe (OPTP) spectroscopy. Our findings reveal that carrier mobilities and diffusion lengths strongly depend on the type of solvent used for the preparation of the mixed cation perovskite film. The mixed cation perovskite film prepared using dimethylformamide/dimethylsulfoxide solvent shows greater mobility and diffusion length compared to γ-butyrolactone solvent. Our findings provide valuable insights to improve the charge carrier transport in mixed cation perovskites through solvent engineering.